Criteria for identification and selection of susceptible Spanish landscapes to be included in the World Heritage list of UNESCO - Víctor Fernández Salinas; Rocío Silva Pérez (Boletín de la Asociación de Geógrafos Españoles, 2015)
Texto resumen.